HPV Test as Test of Cure After Conization for CIN2+: A Nationwide Register-Based Cohort Study. Issue 4 (October 2022) - Bruhn, Lærke Valsøe; Hyldig, Nana; Schledermann, Doris
Abstract : The human papillomavirus test at the first post-treatment control can be used as test of cure for cervical intraepithelial neoplasia grade 2 or worse after stratifying for resection margins. Abstract : Objective: The purpose of this study was to assess if cytology can be omitted in the follow-up after treatment for cervical intraepithelial neoplasia grade 2 or worse (CIN2+) and if human papillomavirus (HPV) test can be used alone as test of cure (TOC) after stratifying for resection margins. Material and Methods: In this retrospective register-based study, women who had a conization performed in Denmark between January 1 and December 31, 2013, were included. Histology, cytology, and HPV test results were obtained from The Danish Pathology Data Bank for a 3-year follow-up. Results: A total of 5, 174 women were included, of whom 6.1% (318/5, 174) had histological residual/recurrent disease in the follow-up period. In the group with free margins, 2.6% (73/2, 780) had residual/recurrent disease in contrast to 10.2% (245/2, 394) in the group with involved margins. In the group with free resection margins and negative HPV test results, residual/recurrent disease was found in 0.5% (13/2, 780) compared with 0.3% (9/2, 780) in the group with negative HPV test results and normal cytology at 6 months′ follow-up. Based on margin status and HPV test result as follow-up, the sensitivity, specificity, and positive and negative predictive values were 95.9%, 43.2%, 10.0%, and 99.4% respectively, and for combined testing (margin status, HPV, and cytology), 97.2%, 41.2%, 9.8%, and 99.6%, respectively. Conclusions: Using the HPV test at the first post-treatment control as TOC for cervical intraepithelial neoplasia grade 2 or worse after stratifying for resection margins in cone resections yields an equally high sensitivity and negative predictive value as cotesting with cytology. We suggest that women with free resection margins return to the routine screening program after negative HPV test result as TOC at 6 months.